Identification of the fracture surface of thermoset polyester due to bending load - Nusyirwan; Mutya Rani; Rully Pratama (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2022)
In this research, an attempt was made to improve the brittle nature of the Unsaturated Polyester (UP) polymer which cannot undergo plastic deformation to be improved to become more resilient by adding Thermoset Vinyl Ester and Methyl Methacrylate (MMA). To show the change in the toughness of the polyester material, a test is carried out to provide a tensile load and a flexural load until the material breaks This work reports the successful fabrication of polyester blends by mixing vinyl esters with different percentages. The test shows that there is a linear relationship between the shape of the fracture surface due to bending loads and observations through SEM which are directly related to the flexural stress properties with the fracture surface morphology. The mixture of polyester with 40% vinyl ester showed the highest flexural stress of 126.88 MPa while for pure polyester of 49.71 MPa this showed an increase of 255.24% compared to pure polyester. This shows that the addition of vinyl ester to polyester resulted in an increase in the toughness of the polyester, but for 100% vinyl ester the return stress decreased by 56.50 MPa. This indicates that due to the breaking of some of the polyester chain networks causes a decrease in the structural stiffness, which results in an increase in the plastic deformation zone fraction.